2011
DOI: 10.1038/eye.2011.221
|View full text |Cite
|
Sign up to set email alerts
|

Pilot randomised controlled trial of face-down positioning following macular hole surgery

Abstract: Objective This was a pilot randomised controlled trial (RCT) to investigate the effect of post-operative face-down positioning on the outcome of macular hole surgery and to inform the design of a larger definitive study. Methods In all, 30 phakic eyes of 30 subjects with idiopathic full-thickness macular holes underwent vitrectomy with dye-assisted peeling of the ILM and 14% perfluoropropane gas. Subjects were randomly allocated to posture face down for 10 days (posturing group) or to avoid a face-up position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 23 publications
2
62
0
1
Order By: Relevance
“…The need for posturing is debated with many studies showing successful non-posturing surgery in holes <400 μm and often with the use of short-acting gases [5,15,16,17,18]. Large holes are still usually treated with longer-acting gases and posturing [5,6,7,19,20] although the requirement for posturing is debated and a further study is needed [21]. For about 3/4 (72%) of our patients' vitrectomy surgery would currently be the only available treatment option but in only approximately a 1/3 of the cases (28.5%), would vitrectomy, ILM peeling, long-acting gas and post-operative face-down posturing be recommended by the majority of surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for posturing is debated with many studies showing successful non-posturing surgery in holes <400 μm and often with the use of short-acting gases [5,15,16,17,18]. Large holes are still usually treated with longer-acting gases and posturing [5,6,7,19,20] although the requirement for posturing is debated and a further study is needed [21]. For about 3/4 (72%) of our patients' vitrectomy surgery would currently be the only available treatment option but in only approximately a 1/3 of the cases (28.5%), would vitrectomy, ILM peeling, long-acting gas and post-operative face-down posturing be recommended by the majority of surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Inner limiting membrane (ILM) peeling has been shown to be beneficial in terms of closure for all macular holes but because of potential side effects some surgeons do not peel in small and medium-sized holes [3,4]. Two randomized controlled trials have shown that post-operative face-down posturing improves hole closure rate in holes >400 μm in size but many surgeons practice non-posturing surgery in those <400 μm [5,6,7]. The mix of macular hole cases thus presenting to surgeons is important in predicting which options will be selected and which resources needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the other, patients had vitrectomy followed by cataract surgery. 21 The purpose of these pilot studies was to estimate the number of patients required to identify a difference in outcome in a definitive trial.…”
mentioning
confidence: 99%
“…Even in an upright position, gas tamponading exerts an effect on MHs as long as gas covers the lesion. However, some of these series did not attain the success rate achieved with standard treatment, especially when the minimum diameter of the MH was greater than 400 µm [3,5,6]. A recent meta-analysis reported slightly higher MH closure rates with 5-10 days of face-down posturing as compared with posturing for 24 h or less, but this difference was not statistically significant [7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported slightly higher MH closure rates with 5-10 days of face-down posturing as compared with posturing for 24 h or less, but this difference was not statistically significant [7]. Yet other reports have demonstrated success rates of 100% for small MHs (<400 µm) either with or without postoperative face-down posturing [6,8,9]. However, perhaps the safest treatment approach is confirmation of MH closure in gas-filled eyes within 24 h before allowing patients to discontinue face-down posturing on day 1.…”
Section: Introductionmentioning
confidence: 99%